Does Motivation Predict Entrepreneurial Behavior In Youth Samples? - Chidinma Nebo; Ekaete Ufeh; Emmanuel Uye (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2026)
Entrepreneurial behavior has become increasingly vital in addressing economic and unemployment challenges in many parts of Nigeria. While studies have used different predictors on entrepreneurial behavior, however, studies linking motivation directly on entrepreneurial behavior are lacking. Therefore, this study examines the predictive role of motivation on entrepreneurial behavior in youth samples. Cross-sectional survey design was adopted while purposive sampling technique was used to select the study population. Data were conveniently collected from 220 youths using validated questionnaires and analyzed using simple linear regression p < .001 level of significance. The result indicates significant influence of motivation on entrepreneurial behavior, F (1, 218) = 45.90, p < 0.001. Further analysis reveals that motivation independently predicts entrepreneurial behavior (β = .658, p <.001). The study concludes that motivation is a robust predictor of entrepreneurial behavior in study participants. The study concludes that the government and private sector should create entrepreneurial hubs and incubators to motivate youths to engage in entrepreneurial behavior.